The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0034-7167-2017-0950
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Ulcer in Intensive Care Units: a case-control study

Abstract: Objective: To evaluate the relationship between presence/absence of Pressure Ulcer, socio-demographic factors and hospitalization. Method: Case-control study, performed through multiple logistic regression based on information from the adverse event reporting system and the hospital information system, between September/2014 and August/2015. Results: Among the risk factors, after adjustment, age greater than or equal to 60 years, hospitalization due to infectious, parasitic and neoplastic diseases, periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0
31

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 22 publications
5
19
0
31
Order By: Relevance
“…In this study, no significant relationship was found between pressure injuries and sex as in other studies (Lichterfeld‐Kottner et al., 2020; Pachá et al., 2018). In our study, it was found that increasing age had a significant effect on pressure injuries and more than 90% of pressure injuries were reported in patients over 60 years of age that the main reason for this issue is due to less mobility and activity of older people.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In this study, no significant relationship was found between pressure injuries and sex as in other studies (Lichterfeld‐Kottner et al., 2020; Pachá et al., 2018). In our study, it was found that increasing age had a significant effect on pressure injuries and more than 90% of pressure injuries were reported in patients over 60 years of age that the main reason for this issue is due to less mobility and activity of older people.…”
Section: Discussionsupporting
confidence: 44%
“…In the intensive care unit, due to long‐term hospitalization, patients' deteriorating condition and decreased level of consciousness, the prevalence of pressure ulcers is higher, which is consistent with the results of a study by Sohrabi et al (Akhkand et al., 2020). Studies show that approximately 60% of pressure injuries occur in the first two weeks of hospitalization in the intensive care unit (Pachá, Faria, Oliveira, & Beccaria, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Erros no processo que envolve a terapia medicamentosa como a ausência da higienização das mãos antes do preparo e administração das medicações podem potencializar o surgimento de outros tipos de eventos adversos na assistência como as infecções (6) . Quando envolvem eventos como lesões por pressão em pacientes hospitalizados podem estar associados pela diminuição da percepção sensorial devido ao excesso de sedativos, analgésicos e relaxantes musculares (18) .…”
Section: Discussionunclassified
“…A estimulação do raciocínio clínico e reflexivo é fundamental no desempenho de habilidades e capacidades imprescindíveis do enfermeiro (13)(14)(15) , as quais são componentes essenciais a serem incorporados à cultura de segurança. Para isso, a educação permanente e continuada deve ser inserida como ferramenta no processo de trabalho para promoção de mudanças no comportamento e postura profissional, determinantes na tomada de decisões assistenciais (16)(17)(18)(19)(20) .…”
Section: Discussionunclassified
“…Os demais (outros) constituíram 18%. A literatura varia nesse aspecto, uma vez que autores observaram, em estudo sobre LPP, que 63% dos agravos associados eram doenças infecciosas, parasitárias e neoplasias (11) . Lembra-se que infecções e neoplasias podem cursar com outros fatores de risco para LPP.…”
Section: Parte 1 -Perfil De Pacientesunclassified